Philanthropy (tabarru’at) in Islam and its four shari’ah objectives - Ali, Mohammed Farid; U Tun Aung, Maulana Akbar Shah; Gamon, Alizaman Dumangcag; Tagoranao, Mariam Saidona (IDOSI Publications, 2018)
In Islam, the term tabarru’at (philanthropy) connote extending of wealth or benefit generating from the wealth to people free of charge out of mere kindness. It is a charitable act befitting the Qur’anic concept of birr (righteousness) mentioned in Chapter al-Ma’idah (5: 2). Donation in Islam is a complex concept because of its varying modes and categories of recipients. In some modes the corpus is donated, whereas some modes restrain the corpus and donate the generating benefit only. Some modes are not restricted to time whereas some modes are specific timewise. The recipients of the donations range from next of kin to total strangers; from Muslims to believers of other faiths. The recipients can be individuals and at the same time communal. Despite the complexity, the Shari’ah has legalized and encouraged the concept of philanthropy in Islam. The higher objective behind this is the pursuit of wellbeing both for individual and for the community. In the maqasid al-shari’ah discourse, specific objective leads to the higher objective of the Shari’ah. This paper intends to unveil the four specific Shari’ah objectives of donations in Islam and explore roles that can serve the humanitarian aid.